Distribution. Mainland SE Asia in Myanmar, Cambodia, Vietnam, and PeninsularMalaysia; also Borneo and Sumatra. in Mustelidae - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
Distribution. Mainland SE Asia in Myanmar, Cambodia, Vietnam, and PeninsularMalaysia; also Borneo and Sumatra. Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Mustelidae, pp. 564-656 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on page 645, DOI: 10.5281/zenodo.5714044